2018
DOI: 10.1369/0022155417749174
|View full text |Cite
|
Sign up to set email alerts
|

Periarteriolar Glioblastoma Stem Cell Niches Express Bone Marrow Hematopoietic Stem Cell Niche Proteins

Abstract: In glioblastoma, a fraction of malignant cells consists of therapy-resistant glioblastoma stem cells (GSCs) residing in protective niches that recapitulate hematopoietic stem cell (HSC) niches in bone marrow. We have previously shown that HSC niche proteins stromal cell-derived factor-1α (SDF-1α), C-X-C chemokine receptor type 4 (CXCR4), osteopontin (OPN), and cathepsin K (CatK) are expressed in hypoxic GSC niches around arterioles in five human glioblastoma samples. In HSC niches, HSCs are retained by binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 217 publications
2
53
0
1
Order By: Relevance
“…We identified peri-arteriolar GSC niches in sections of GBM samples based on immunohistochemical localization of cancer stem cell marker CD133, smooth muscle actin (SMA) as smooth muscle cell marker and cytokine SDF-1α, which have been shown to be associated with GSC niches (Hira et al 2015 , 2018b ) (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified peri-arteriolar GSC niches in sections of GBM samples based on immunohistochemical localization of cancer stem cell marker CD133, smooth muscle actin (SMA) as smooth muscle cell marker and cytokine SDF-1α, which have been shown to be associated with GSC niches (Hira et al 2015 , 2018b ) (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Juxtacrine signaling between endothelial cells and GBM cells (Calabrese et al 2007 ) is crucial to maintain the stem cell phenotype of GSCs (Zhu et al 2011 ; Schiffer et al 2014 ; Roos et al 2017 ). Recently, the different types of cancer stem cell niches, such as peri-vascular, peri-hypoxic, peri-immune, ECM and peri-arteriolar niches were integrated into one concept, the hypoxic peri-arteriolar GSC niche (Hira et al 2018a ), which mimics the HSC niche in bone marrow (Hira et al 2018b ). In the same study, GSC niches were found around 2% of the arterioles and 0% of venules and capillaries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This explains the hypoxic areas that express hypoxia-inducible factor (HIF)-1α and vascular endothelial growth factor (VEGF) in which we found all periarteriolar niches adjacent to necrotic areas. 21,71 Second, members of the Notch family drive the arterial gene program, whereas the orphan receptor COUP-TFII suppresses this program and regulates venous specification. The homeobox gene Prox-1 encodes for the master switch of lymphatic specification.…”
Section: Arterioles Capillaries Venules and Lymph Vesselsmentioning
confidence: 99%
“…Because of the homology of the hypoxic peri-arteriolar HSC niches in bone marrow and the hypoxic peri-arteriolar GSC niches in glioblastoma tumors, we postulate the hypothesis that plerixafor treatment in combination with standard therapies is beneficial for glioblastoma patients as well. This hypothesis is based on the assumption that plerixafor treatment can mobilize GSCs out of their protective niches, which results in GSC differentiation and their sensitization to radiotherapy and chemotherapy [8,12,13,15]. In a single-arm phase I/II clinical trial including 29 glioblastoma patients, intravenous administration of plerixafor was combined with radiotherapy and temozolomide chemotherapy [35,36].…”
mentioning
confidence: 99%